Penerapan Model Application of Step Instruction and Elaboration (APPOSITE) untuk Meningkatkan Hasil Belajar Kognitif Siswa SMA pada Materi Suhu dan Kalor - Nur Kamila; Sri Handono Budi Prastowo; Lailatul Nuraini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine the differences in the improvement of cognitive learning outcomes of students using the APPOSITE model and students using the direct instruction model. This research is an experimental study with a pretest-posttest control group design. The research subjects were students of class XI IPA at SMA Muhammadiyah 3 Jember. The sample in this study were students of class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Data collection techniques are carried out through tests, observation, interviews and documentation. The data analysis technique used the N-gain test and t-test. Based on the results of the N-gain analysis, it can be seen that the class that uses the APPOSITE model gets a score of 0.36 in the moderate category, while the N-gain class that uses the direct instruction model gets a score of 0.22 in the low category. Based on the results of hypothesis testing using the independent sample t-test can be concluded that there is a significant difference between the increase in cognitive learning outcomes of students using the APPOSITE learning model and the improvement of student cognitive learning outcomes using the direct instruction learning model.Keyword: APPOSITE model, cognitif learning outcomesABSTRAK.Penelitian ini bertujuan untuk mengetahui perbedaan peningkatan hasil belajar kognitif siswa yang menggunakan model APPOSITE dengan siswa yang menggunakan model direct instruction. Penelitian ini merupakan penelitian eksperimen dengan desain Pretest-Posttest Control Group Design. Subjek penelitiannya adalah siswa kelas XI IPA di SMA Muhammadiyah 3 Jember. Sampel dalam penelitian ini adalah siswa kelas XI IPA 1 sebagai kelas eksperimen dan siswa kelas XI IPA 2 sebagai kelas kontrol. Teknik pengumpulan data dilakukan melalui tes, observasi, wawancara dan dokumentasi. Teknik analisis data menggunakan uji N-gain dan uji t-test. Berdasarkan hasil analisis N-gain terlihat bahwa kelas yang menggunakan model APPOSITE memperoleh skor 0,36 dengan kategori sedang, sedangkan N-gain kelas yang menggunakan model direct instruction memperoleh skor 0,22 dengan kategori rendah. Berdasarkan hasil uji hipotesis menggunakan uji independent sample t-test dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara peningkatan hasil belajar kognitif siswa yang menggunakan model pembelajaran APPOSITE dengan peningkatan hasil belajar kognitif siswa yang menggunakan model pembelajaran direct instruction. Kata kunci: model APPOSITE, hasil belajar kognitif